My red balloon - Yamada, Kazuaki (Minedition, 2014)
"A little girl begins a happy bus outing with her beautiful red balloon. But when the balloon suddenly flies away, the bus driver and a passenger bear gallantly help follow the balloon. A wild chase begins and along the way a rabbit, a polar bear, a penguin, and a giraffe all join in to help as they follow the wayward balloon. And when a bird pecks the balloon with its beak, the result makes all their effort seem in vain, but the little girl's new friends once again come to the rescue with just the right words of comfort."--Publisher's description.